Youth Attitudes who’s working in civil society organizations in Aden Governorate: Toward Voluntary Work - Al-Tayar, Mohamed Awad (Journal of Humanities & Social Sciences, 2020)
This research aims to know the attitudes of youth towards the practice of volunteering in the governorate of Aden in respect of some variables. The researcher used the descriptive analytical approach as the appropriate approach that is compatible with the nature of the phenomenon studied and the study sample consisted of (150) young men and women working in the field of volunteer work in the governorate of Aden including (86) males and (64) females. The questionnaire was considered the main tool for collecting the required data, and the results of the research showed that the more the goals of volunteer work were clear, the more youth’s turnout to join the volunteer work increase with an average arithmetic and the response for the sample answers was (3.98), the positive results showed in the directions of the members of the research sample toward the volunteer work in a way that created in them a motivation to join in the different fields with an arithmetic average of (3.68). This represents a high degree of appreciation according to the Likert quintet. The educational field ranked first, followed by security and defense, then the environmental field, as well as the health and social field. The results also indicated that the most important difficulties and obstacles facing youth volunteering are represented in the absence of family upbringing that promotes volunteer behavior and economic and social conditions. The results showed that the most important reasons for refraining from volunteer work are the lack of motivation and encouragement, the multiplicity of bureaucratic complications, the spread of a culture of defect, the absence of fixed programs to care for and organize volunteers, the lack of sufficient time and the spread of corruption, the failure to understand the nature of voluntary work and the community’s need for it and finally the fear of failure. And this result came with a general average (3.34) representing the degree of estimation of impartiality, as the results of the research showed that the most important effects of volunteering is represented in the development of volunteerism, a feeling of self and the imposition of youth to express themselves and unleash their energy and creativity and provides them with the necessary skills and experience in the ability to plan and manage solutions to the problems facing them, and the results indicated that there are statistically significant differences between female males about the goals of volunteer work and the reasons for youth’s reluctance to volunteer work at the level of significance (α≤0.05) and the absence of significant statistic differences between youth attitudes towards areas of volunteer work that they love and the effects of volunteer work on them and on society at the level (α≤0.05).